Elektronische Verordnungssysteme auf pädiatrischen Normalstationen - Wimmer, Stefan; Toni, Irmgard (Monatsschrift Kinderheilkunde, 2022)
Background: Computerized physician order entry (CPOE) systems are used more and more frequently in pediatric hospitals. The reasons are optimized patient care and documentation as well as the potential reduction of adverse drug reactions (ADR) caused by medication errors; however, for the implementation on pediatric wards special technical requirements for the software have to be considered to avoid danger to patients due to software or user errors. Aim of the study: The available literature on the use of CPOE systems on general pediatric wards was analyzed with respect to the influence on ADR. Methods: A structured literature search with defined inclusion criteria was carried out in PubMed. Results: Out of 181 search results 4 studies met the inclusion criteria. None of the three studies from the USA and the one from Hong Kong could show a significant reduction of clinically relevant ADRs or medication errors with harm; however, three studies reported a significant positive effect on potentially harmful medication errors. These results correspond to our own data that have so far not been published in a journal. Discussion: Overall, the available studies showed a positive effect on the frequency of medication errors. The use of CPOE systems seems to be meaningful on general pediatric wards on condition that the software is suitable and the personnel are comprehensively trained.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Adverse drug reaction; Clinical decision support; Documentation; Medication error; Patient care